2017
DOI: 10.1007/s13355-017-0527-7
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on distributions and oviposition sites of Drosophila suzukii (Diptera: Drosophilidae) and its parasitoids on wild cherry tree in Tokyo, central Japan

Abstract: Distributions and oviposition sites of Drosophila suzukii (Matsumura) and its parasitoids on wild cherry tree were studied in early summer in the suburbs of Tokyo, central Japan. Adults of D. suzukii occurred in the foliage layer as well as in the undergrowth layer. The number of D. suzukii that emerged did not significantly differ between wild cherry fruit collected from the foliage layer and those from the undergrowth layer. In addition, the number of D. suzukii that emerged per fruit decreased when fruit we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 18 publications
1
35
0
1
Order By: Relevance
“…The same Ganaspis cf. brasiliensis is the main larval parasitoid of D. suzukii in South Korea (Daane et al 2016 ), Japan (Kasuya et al 2013a ; Wachi et al 2015 ; Matsuura et al 2017 ) and China (Girod et al 2018b ), where it probably also attacks two other fruit-inhabiting drosophilids, D. pulchrella and D. subpulchrella , the two sister species of D. suzukii .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same Ganaspis cf. brasiliensis is the main larval parasitoid of D. suzukii in South Korea (Daane et al 2016 ), Japan (Kasuya et al 2013a ; Wachi et al 2015 ; Matsuura et al 2017 ) and China (Girod et al 2018b ), where it probably also attacks two other fruit-inhabiting drosophilids, D. pulchrella and D. subpulchrella , the two sister species of D. suzukii .…”
Section: Discussionmentioning
confidence: 99%
“…Both populations happily attacked and developed in larvae of D. melanogaster, D. subobscura and D. suzukii in all substrates but not in the four other hosts, with the exception of one successful development in a D. immigrans larva. Leptopilina japonica frequently parasitized larvae of D. suzukii in Japan (Novković et al 2011 ; Matsuura et al 2017 ), South Korea (Daane et al 2016 ) and China, where it probably attacks also larvae of D. pulchrella and D. subpulchrella (Girod et al 2018b ). In Japan, it is also found on D. biauraria and D. rufa and it has been successfully reared on D. simulans in the laboratory (Novković et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rohlfs and Hoffmeister (2004) suggested that the inverse density-dependent parasitism could occur if individuals occurring within resources are less likely attacked than those exposed to parasitoids at surface. In our previous studies (Mitsui et al 2007;Kasuya et al 2013a,b;Kimura 2015;Matsuura et al 2018), however, the parasitism rate is not so high in drosophilid flies exploiting patchily distributed fruit and mushroom in central Japan. It is not certain whether the parasitism rate reaches the level at which the Rohlfs and Hoffmeister's (2004) mechanism works.…”
Section: Discussionmentioning
confidence: 72%
“…,b; Kimura ; Matsuura et al . ), however, the parasitism rate is not so high in drosophilid flies exploiting patchily distributed fruit and mushroom in central Japan. It is not certain whether the parasitism rate reaches the level at which the Rohlfs and Hoffmeister's () mechanism works.…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, cherries had been detached from plants. However, these fruits are no longer economically viable and SWD preferentially oviposit in attached fruit . Therefore, it is recommended that future work focuses on attached fruit.…”
Section: Discussionmentioning
confidence: 99%